The Effect of External Public Debt and State Sukuk (SBSN) On Indonesia's Economic Growth: An Autoregressive Distributed Lag Approach - Listiyani, Fahmaninda; Sriyana, Jaka; Ratnawati, Nirdukita (Dinasti International Journal of Economics, Finance & Accounting, 2023)
Indonesia's external public debt continues to grow with a ratio of 30.1% of GDP. In the first quarter of 2023, Indonesia's external public debt reached 199.4 billion US dollars or equivalent to 3000 trillion rupiahs. This condition makes Indonesia a debtor country that depend on international creditor countries or institutions. In addition, state sukuk as an alternative to state financing with sharia guidelines also continues to grow, but its performance cannot be equal to external public debt as one of the pillars of Indonesia's economic growth. Therefore, this study is present to analyse the effect of government external public debt paired with state sukuk as an Islamic fiscal variable on Indonesia's economic growth. Moreover, this study also analyses the factors that influence the growth of Indonesia's external public debt. The sample used to analyse the effect of government external public debt and state sukuk on Indonesia's economic growth was taken from the first quarter of 2010 to the first quarter of 2023. This study uses Autoregressive Distributed Lag (ARDL) to find empirical finding of the model. The results of this study indicate that the external public debt variable in the long term has a significant negative effect on economic growth while the state sukuk variable in the long term has no effect on economic growth.